Ethanol Extract of Root of Prunus persica Inhibited the Growth of Liver Cancer Cell HepG2 by Inducing Cell Cycle Arrest and Migration Suppression. (12th October 2017) - Shen, Hongchun; Wang, Honglian; Wang, Li; Wang, Lu; Zhu, Menglian; Ming, Yao; Zhao, Sha; Fan, Junming; Lai, En Yin
Abstract : Liver cancer is the second most lethal cancer and hepatocellular carcinoma (HCC) is the primary cancer subgroup. However, the current chemotherapy agents remain ineffective and present wide side effects for advanced HCC patient. In this study, we investigated the antitumor role of ethanol extract of root of peach tree ( Prunus persica (L.) Batsch and hereafter designated as TSG in short of its Chinese name), which is an important ingredient in Chinese medicine prescription, in liver cancer cell HepG2. By cell viability assay, we showed that addition of TSG in the culture medium inhibited the cell growth of HepG2 cells in a dose and time-dependent way. Cell cycle analysis indicated that TSG caused sustained M/G2 phase arrest. The expression of mitosis-related protein Cdc25c was impaired upon TSG treatment. Furthermore, wound healing assay demonstrated that TSG treatment notably suppressed the migration of HepG2 cells and the expression of extracellular matrix metalloprotease, MMP3 and MMP9. Most significantly, administration of TSG inhibited in vivo tumor growth in nude mice. Our findings suggested that TSG may serve as a source to isolate anti-HCC therapeutic ingredients.